3x+9x-7=3(4x+4)

Simple and best practice solution for 3x+9x-7=3(4x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9x-7=3(4x+4) equation:


Simplifying
3x + 9x + -7 = 3(4x + 4)

Reorder the terms:
-7 + 3x + 9x = 3(4x + 4)

Combine like terms: 3x + 9x = 12x
-7 + 12x = 3(4x + 4)

Reorder the terms:
-7 + 12x = 3(4 + 4x)
-7 + 12x = (4 * 3 + 4x * 3)
-7 + 12x = (12 + 12x)

Add '-12x' to each side of the equation.
-7 + 12x + -12x = 12 + 12x + -12x

Combine like terms: 12x + -12x = 0
-7 + 0 = 12 + 12x + -12x
-7 = 12 + 12x + -12x

Combine like terms: 12x + -12x = 0
-7 = 12 + 0
-7 = 12

Solving
-7 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8t+40+16t-49=18t+23 | | 18x-12=3x^2 | | 7+6*2-2+8= | | 7a+21b=110 | | 2(1/6)*(3/26) | | d=85(4h) | | 34+32a-50=23a+26 | | 6x+6=6x+5 | | 2l+2w=98.2 | | 5-6y=35 | | -12720+200= | | 4/7x-1/3=1/5 | | 46.25/60= | | -11+x=-7x-8x+-8(-x+1) | | 7b+33+b+50=19b | | -7(-4x)=-4x+9 | | 6(2x-7)=3(5x-8) | | 8(y+8)=-4.3 | | -5c-4+7c=60 | | k[x]=6x+100k | | 9/x=11/7 | | 28+x(21)=35 | | 2x-32=5x+1 | | 1=k*5 | | 4x-2x-76=3x+11 | | 2(3x-4x+1)=8x | | 7/12a=13/14 | | 3k/287=2/3 | | -4x-4x=-7x+6 | | 4=2-36 | | 8p-5=67-9 | | -11-5a=6-(5a+4) |

Equations solver categories